Diagonal and off-diagonal types of disorder in condensed matter theory - Rudavskii, Yu.; Ponedilok, G.; Petriv, Yu. (Condensed Matter Physics, 2000)
In the paper we investigate the distribution function of a diagonal type of
disorder, their relation with microscopic model parameters and structural
correlation functions. The conditions are obtained for which the distribution of random values of atomic energy levels will be of Gauss type. The
numerical analysis of dispersion D is performed. The distribution to the
hydrogen-like atom chemisorption on an amorphous system is applied. В статтi дослiджується функцiя розподiлу дiагонального типу безладу, її зв’язок з мiкроскопiчними параметрами моделi та структурними кореляцiйними функцiями. Отриманi умови, при яких розподiл випадкових величин атомних енерґетичних рiвнiв буде гауссового типу. Проведений чисельний аналiз дисперсiї D . Розподiл застосований до проблеми хемосорбцiї водневоподiбних атомiв на аморфнiй
поверхнi.